Social marketing campaigns content characteristics in order to promote pet welfare - Moyano, Gina; López Ruiz, Javier; Morán Cárdenas, Gina (Scripta Mundi, 2025)
Animal welfare refers to the recognition of the rights and freedoms of animals to live in an environment that allows them to achieve a positive mental and physical state, satisfying their basic needs. This topic gained greater notoriety since the identification of the “Five Freedoms of Animals” and the subsequent creation of principles and standards between the 1960s and 1970s. However, despite the growing interest, a large part of the population remains unaware of these rights, making education and engagement essential to raising awareness. In this context, “social marketing” is emerging as an effective communication strategy to promote changes in society’s perceptions, behaviors, and values regarding the treatment of animals. Based on the pillars of education and engagement, this study seeks to identify the characteristics that marketing content should have in order to achieve greater reach and effectiveness.An exploratory and conclusive descriptive research methodology was applied. The exploratory phase consisted of a documentary review of qualitative and quantitative data, while the descriptive phase was developed through interviews with three organizations focused on animal welfare and trough a survey to Ecuadorian citizens. The survey was implemented with a probabilistic approach (94% confidence level). The results show that organizations prioritize content that promotes adoption and volunteering; while citizens consider effective campaigns that tell the stories of rescued animals, using formats such as videos, photographs, and documentaries for campaigns that encourage the involvement. For educational purposes, respondents considered it essential to provide information about pet care, the consequences of abandonment, and responsible adoption, preferably in visual formats and articles.